2004
DOI: 10.1073/pnas.0306587101
|View full text |Cite
|
Sign up to set email alerts
|

The tissue plasminogen activator-plasmin system participates in the rewarding effect of morphine by regulating dopamine release

Abstract: Tissue plasminogen activator (tPA) is a serine protease that catalyzes the conversion of plasminogen (plg) to plasmin, which in turn functions to degrade extracellular matrix proteins in the central nervous system. The tPA-plasmin system plays a role in synaptic plasticity and remodeling. Here we show that this protease system participates in the rewarding effects of morphine by acutely regulating morphine-induced dopamine release in the nucleus accumbens (NAcc). A single morphine treatment induced tPA mRNA an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
130
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(140 citation statements)
references
References 41 publications
9
130
0
Order By: Relevance
“…Furthermore, both PAR1 (Striggow et al, 2001), and NMDA receptor subunits (Ishii et al, 1993) are highly expressed in brain regions involved with emotional learning, including hippocampus and amygdala. These results it well with suggestions that serine proteases can impact learning (Baranes et al, 1998;Pawlak et al, 2002;Nagai et al, 2004Nagai et al, ,2006Pang et al, 2004;Pawlak et al, 2005), and may suggest that PAR1 is a substrate at which serine proteases such as plasmin exert their actions.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Furthermore, both PAR1 (Striggow et al, 2001), and NMDA receptor subunits (Ishii et al, 1993) are highly expressed in brain regions involved with emotional learning, including hippocampus and amygdala. These results it well with suggestions that serine proteases can impact learning (Baranes et al, 1998;Pawlak et al, 2002;Nagai et al, 2004Nagai et al, ,2006Pang et al, 2004;Pawlak et al, 2005), and may suggest that PAR1 is a substrate at which serine proteases such as plasmin exert their actions.…”
Section: Discussionsupporting
confidence: 86%
“…tPA−/ − mice also showed deficits in hippocampal learning that were reversed by tPA administration (Pawlak et al, 2002). Both tPA −/− and plasminogen −/− mice showed deficits in conditioned reward (Nagai et al, 2004). Plasmin expression and function are also necessary for activation of brain-derived neurotrophic factor (BDNF) from its propeptide form.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings are consistent with those of Nagai et al 22 who used SDS-PAGE-based zymography to show that subcutaneous administration of morphine increased tPA activity in numerous compartments of the mouse brain at a similar time point. 22 Interestingly, we observed that the single injection of morphine caused tPA activity in the cerebellum to decrease by approximately 27% compared with saline-treated controls (Figure 2). Using realtime PCR reaction, we also demonstrated that tPA mRNA levels followed a similar trend and were marginally higher in the cortex, significantly increased in the sub-cortical structures (Po0.05) and lower in the cerebellum (Supplementary Figure S4).…”
Section: Changes In Brain-derived Tpa Activity In Vivo Following Cns mentioning
confidence: 91%
“…The Changes in tPA after CNS injury or stimulation M Sashindranath et al downregulation of cerebellar tPA activity following morphine administration was unexpected given that morphine has previously been shown to upregulate tPA levels in the nucleus accumbens, striatum and limbic system. 22 Furthermore, tPA activity in the nucleus accumbens is involved in the rewarding and locomotor-stimulating effects of morphine. 22 Notably, morphine has recently been identified as an endogenous neuromodulator in the mouse cerebellum, in which GABAergic basket cells release morphine onto the m-opioid receptors of Purkinje neurons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation